Khitan Tradition among Muslims: Integrating Ibnu Hajar's Thought and Modern Science: Tradisi Khitan di Kalangan Umat Islam: Integrasi antara Pemikiran Ibnu Hajar dan Sains Modern - Yazofa, Tartila; Ahmad Zuhri; Juli Julaiha (Jurnal Living Hadis, 2024)
The practice of circumcision among the Muslim community began during the time of Abraham (peace be upon him) and continues for generations to this day. This reality makes circumcision no longer limited to practice but has been transformed into a living tradition in the community. This is also corroborated by the prophet's hadith which mentions circumcision as one of the five human natures, including part of the process of becoming an adult. However, many children and infants have been circumcised. This phenomenon eventually raises the question: what is the rule of circumcision in Islam, and when is the prescribed time for a Muslim to perform circumcision?. These questions will be analyzed through a descriptive-analytical approach based on library research to find the answers that are comprehensive, scientific, and in line with Islamic rules. In this case, Ibn Hajar's thoughts in Kitab Fath al-Bari become the main source of study, supported by several relevant studies. The results show that the original law of circumcision is mustahab and then becomes obligatory when a person reaches the age of puberty. As for the timing of circumcision, Islam does not specify the ideal circumcision. A person can be circumcised when he is a toddler, a child, and maximum when he is a teenager who enters the age of puberty. The timing is more inclined to the doctor's recommendation so that the circumcision process causes bigger problems in the future.